PUS1 is a novel biomarker for predicting poor outcomes and triple-negative status in breast cancer - Fang, Zheng; Shen, Hong-yu; Xu, Qi; Zhou, Hong-lei; Li, Lei; Yang, Si-Yuan; Zhu, Zhen; Tang, Jin-hai (Frontiers in Oncology, 2022)
Breast cancer patients' outcomes have improved dramatically in recent years, but relapses and poor prognosis remain common due to its aggressiveness and heterogeneity. The development of reliable biomarkers is still needed for predicting prognosis and treatment effectiveness. Recently, a growing body of research suggests that pseudouridine synthases contribute to the development of many cancers, but their contribution to breast cancer remains largely unknown. Using an integrative analysis, we selected PUS1 as the candidate biomarker. A tissue microarray of 131 breast cancer patients was then utilized to determine the clinical significance and prognostic value of PUS1. RNA sequencing analysis was conducted to identify downstream genes that differ between control and PUS1 knockdown cells. The effect of PUS1 on phenotypes of cells was assessed using cell proliferation, colony formation, and transwell invasion assays. We found that breast tumors overexpressed PUS1 compared with paired normal tissues. PUS1 expression was positively correlated with TNBC status (P= 0.020) and tumor grade (P <0.0001), but not with age (P= 0.736), tumor size (P= 0.608), lymph node (P= 0.742), ER (P= 0.162), PR (P= 0.901), HER (P= 0.608) or tumor stage (P= 0.411). Comparatively, patients with high PUS1 levels had shorter overall survival time (P=0.0001) and relapse-free survival time (P = 0.0093). A univariate and multivariate survival analysis suggested that the overall survival of patients was independently influenced by the PUS1 score (Univariate Cox P <0.0001, HR=5.176, 95% CI =2.420-11.07; Multivariate Cox P = 0.001, HR = 5.291, 95% CI =1.893-14.78). RNA sequencing data revealed the PUS1 knockdown significantly affects a series of cancer related biological process such as regulation of cell proliferation and cell migration, as well as KEGG pathways including Mitophagy and PI3K-Akt signaling. In vitro, knockdown of PUS1 significantly suppressed the proliferation and colony formation abilities of MDA-MB-231 cells and BT-549 cells. Additionally, the ability of tumor cells to invade was remarkably attenuated in low PUS1 expression groups compared with the corresponding control groups. Our results suggested that PUS1 is a novel biomarker that predicts poor outcomes in patients with breast cancer and may prove to be a promising treatment target.